Implementation of Evidence-Based Cesarean Section (CS) Technique [10H]. (May 2018) - Kaye, Madeline R.; Rieger, Mary; Gavrizi, Sarah; Harkins, John; Keller, Whitney; White, Amanda
Abstract : INTRODUCTION: Despite evidence supporting specific CS operative techniques, usage is poor. We aimed to observe the effect of a QI initiative on evidence-based operative techniques uptake and its impact on postoperative pain, operative time and estimated blood loss (EBL). METHODS: Literature review identified blunt fascial dissection, lack of bladder flap, passive placental delivery, no peritoneal closure, and sutured skin closure as best practice operative techniques. The QI initiative identifying these practices was disseminated through written communication and large group discussion, including both faculty and trainees. Chart review abstracted demographic data, adherence to evidence-based techniques, operative time, post-operative pain scores at 48 hours, and pre- and post-operative hemoglobin for the 6 months before and after the QI initiative. RESULTS: 509 cases met inclusion criteria; 256 prior to QI and 203 following. After QI, blunt facial dissection increased (13.4 to 41.6%, p=0.00), bladder flap creation decreased (25.4 to 12.3%, p=0.0002), manual placental extraction decreased (75.6 to 48.2%, p=0.00), peritoneal closure decreased (46.5 to 32.8%, p=0.0016), and subcuticular skin closure increased (77 to 89.7%, p=0.0001) (all controlled for baseline differences between groups). Operative time, postoperative pain measures, and EBL did not change after the QI initiative. Controlling for all other factors, blunt fascial dissection was associated with decreased operative time (p=0.00) and increased post-op pain at 48 hours (p=0.01). CONCLUSION: Dissemination of recommendations from a QI initiative resulted in increased uptake of best practice operative techniques, although with varying effects on measured operative outcomes. Our project demonstrates the need for continued efforts in standardization of operative technique.